Measuring teacher immediacy and communication competence on student achievement in calculus: a sequential explanatory mixed method design - Barclay, Allen C., author; Gloeckner, Gene W., advisor; Waite, Alina M., committee member; Timpson, William M., committee member; McGrew, John C., committee member (Colorado State University. Libraries, 2012)
On a national level, data indicate that about 40 percent of students in calculus courses finish with a grade of D or F, drop the course, or withdraw (Reinholz, 2009). This high failure rate has led to research studies investigating the teaching of calculus at the national level (House, 1995). Calculus courses have a history of high failure rates, low exam scores, and multiple course redesigns. This paper explored the relationship between teacher immediacy and communication competence from the student perspective on student achievement in calculus. Instead of focusing on course content, reform can come from revisions of the delivery method or instructor behaviors to improve student achievement. Previous studies focused on instructor behaviors and the motivation of teachers and efficacy (Gorrell, 1990; Schaller, 1993) from the instructor perspective. These studies lack student perspective. Calculus for Physical Scientists I at Colorado State University is currently in the process of reform (Klopfenstein, 2008). Past research (House, 1995; Reinholz, 2009; Pilgrim, 2010) has identified the need for reform. Research conducted to help students prepare, perform better, or understand concepts at a higher level, could be beneficial to the fields of Mathematics, Engineering, and Education. Overall, any research conducted to improve failure rates in calculus would be beneficial. Although, findings from this study did not show a statistically significant relationship between student achievement, teacher immediacy, and communication competence, the qualitative findings did show that students who were interviewed enjoyed learning tough concepts, such as calculus, from instructors who used these skills. By using a sequential explanatory design mixed methods study, student opinions expressed in the interviews and focus groups showed a desire for instructors to employ teacher immediacy and communication competence skills. Ruling out instructor behavior as a factor in explaining student achievement, including teacher immediacy and communication competence, may help direct future research to focus on competing theories.
Keywords: calculus; development; instructor; teacher